(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the distal foreland region of central Argentina the Mio-Pliocene continental record is widely distributed (Fig. 1a, Folguera and Zárate, 2009). In La Pampa province it is represented by the Cerro Azul Formation (Fm) (Linares et al., 1980; Visconti, 2007) that involves the lapse between ca. 12-11? Ma and5.8 Ma (Verzi and Montalvo, 2008; Folguera and Zárate, 2009). This lithostratigraphical unit crops out along the walls and floors of the transversal valleys (Calmels, 1996) situated in the central-eastern sectorof La Pampa province. The deposits are blanketed by aeolian silty sands and sandy silts mantles which together with the sand dunes systems usually located along the transversal valleys are considered of Late Pleistocene-Holocene age (Zárate y Tripaldi, 2012).According to Visconti (2007) the outcrops of the Cerro Azul Fm consist of lacustrine, aeolian and fluvial facies. The lacustrine facies, made up of laminated claystones and sandy siltstones to very fine sandstones, have been stratigraphically placed at the base of the Formation. However, field work allowed recognizing the existence of similar deposits making up comparable geoforms at different absolute altitudes in several transversal valleys. This paper is focused on the sedimentological characteristics of these deposits and questions their stratigraphic position. Based on the observations and previous work, three working hypothesis are considered: the deposits are the oldest exposed stratigraphic sections of the Cerro Azul Fm as already stated; the deposits post date the valleys formation, hence they were accumulated within the valleys; the deposits represent similar and diachronic sedimentary settings during the accumulation of the Cerro Azul Formation.The study consisted of a sedimentological-pedo- logical description and sampling coupled with the geomorphological analysis of the deposits at several localities in different transversal valleys of La Pampa (Fig. 1b). Textural, mineralogical (X-Ray difractometry) and micromorphological analyses of thin sections were carried at selected samples. A lithofacies approach was used to describe the deposits resulting in the identification lithofacies (Table 1) and facies associations following Miall’s (2006) proposal, with a partially modified lithofacies code. InterpretationsweremadefollowingMiall (2006), Reading (1996) and Nichols (2009). Two main geomorphic systems (SE1 and SE2) of different altitude are identified in the Nerecó, Hucal, Quehué and Chapalcó valleys (Figs. 1b, 2a) resulting in a characteristic stepped topography. The deposits under study compose the SE2 with a relative height between 2 and 5 m above the valley floor, surrounding the deepest part of them; the lower stratigraphic contact remains unexposed. They are made up of unconsolidated sandy silt, silt and, secondarily, silty fine sand, either massive or with rare planar laminar bedding at some localities, while a dominant angular blocky structure is presentat exposed sections. In some exposures, the deposits under study are featured by the occurrence of cutans and slickensides. Calcium carbonate is commonly present as powdery accumulations, nodules and concretions. Theorganicmattercontentvariesfrom0.03 to 1.17 %. At some levels the deposits exhibit layers of darker colors and higher concentration of organic matter with subprismatic secondary structure when dried. According to the grain-size and primary and secondary structures several lithofacies have been identified: Afm(f), Afb, Lab(c), Lab(mf), Lam(i), Lb(fc), Lal, Lab(cP), Afb(mfP) (Table 1), which were grouped into two main facies, A and B. Facies A represents abandoned channels of low relief and non- channelized areas linked to low energy ephemeral streams/flows transporting sediments to the deepest part of the landscape. Facies B is interpreted as a paludal-like setting corresponding to poorly drained low energy aggradational environments. Both facies are gathered into facies association 1 (FA1), recognized in all the studied localities. It is interpreted as the record of low energy ephemeral fluvial and paludal-like environments, including episodes of higher water inputs linked to heavy rain events. This together with the geomorphological setting of the deposits suggests the occurrence of an aggradational process of low energy during the late Miocene in the interior of the valleys once they were already formed.